The Comprehension of Headed and Headless Relative Clauses in Mandarin: Evidence from Monolingual and Mandarin-English Heritage Bilingual Children. - Zhang, Shijie; Tantucci, Vittorio; Brandt, Silke (Language Learning & Development)
For head-initial languages like English, there is a strong consensus that subject relative clauses (RCs) are acquired earlier and are processed more easily than object RCs. However, for head-final languages like Mandarin, theoretical predictions and findings are in conflict on whether there is a universal subject preference. Moreover, less attention has been given to language-specific factors like the omission of head nouns that might influence RC processing in Mandarin. This study examined the comprehension of headed and headless subject and object RCs in Mandarin by Mandarin-English heritage bilingual (4;00-10;11) and their vocabulary-matched monolingual children (4;00-5;09). The results show that in the character-sentence matching task, both bilinguals and monolinguals comprehended subject RCs more accurately than object RCs, as the similarity between object RCs and simple SVO transitives led to the incorrect head noun assignment. Moreover, this subject RC advantage was not influenced by the omission of the head noun, indicating that bilinguals and monolinguals as young as four years were able to recover omitted head nouns from the context. Compared to monolinguals, bilinguals who were more English dominant made more errors in head noun assignment for Mandarin object RCs, suggesting that both SVO transitives in English and language dominance contribute to cross-linguistic influence.